2023
DOI: 10.1136/bmjoq-2022-002029
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the patient safety culture at a tertiary care hospital in Pakistan using the Hospital Survey on Patient Safety Culture (HSOPSC)

Abstract: BackgroundPatient safety is a top priority for many healthcare organisations worldwide. However, most of the initiatives aimed at the measurement and improvement of patient safety culture have been undertaken in developed countries. The purpose of this study was to measure the patient safety culture at a tertiary care hospital in Pakistan using the Hospital Survey on Patient Safety Culture (HSOPSC).MethodsThe HSOPSC was used to measure the patient safety culture across 12 dimensions at Aga Khan University Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…For a positive patient safety culture, a blame-free, fear-free, and error-reporting environment should be imposed. This finding was in agreement with other studies in India, Saudi Arabia, Pakistan, and Afghanistan [19,[22][23][24][25].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…For a positive patient safety culture, a blame-free, fear-free, and error-reporting environment should be imposed. This finding was in agreement with other studies in India, Saudi Arabia, Pakistan, and Afghanistan [19,[22][23][24][25].…”
Section: Discussionsupporting
confidence: 94%
“…This workload causes chronic fatigue, increasing the possibility of errors and side effects on patient safety. This was consistent with previous studies that reported low scores in the staffing dimension [22,24,25].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Studying the incidence and prevalence of AEs within a health system is an effective way to gauge the status of patient safety. Historically, this has been achieved using incident reporting systems and retrospective chart reviews to record error prevalence [ 32 , 33 ], health consumer and provider surveys [ 19 , 23 , 34 ], and by studying medical litigation cases [ 35 ]. There is a considerable amount of literature from high-income countries that highlights the incidence and impact of AEs in health care [ 2 , 27 , 36 ], however, the same is not true for LMICs [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…LMICs can greatly benefit from initiatives like the Global Patient Safety Collaborative and PSFHF and from using tools such as the HSOPSC and HCAHPS, to perform comprehensive risk assessments of their hospitals, deliver patient safety education and training, establish a culture of safety, and expand the capacity for patient safety within their hospitals [ 23 ]. The generalizability of these standardized, validated tools makes them easily adaptable to the local context and can help evaluate patient safety standards across varying health systems.…”
Section: Introductionmentioning
confidence: 99%